IOT AND THE ISSUE OF DATA PRIVACY - Ashok Kumar Reddy Nadikattu (International Journal of Innovations in Engineering Research and Technology, 2018)
Internet of Things (IoT) can revolutionize the way people live in various sectors that deal with connected devices such as entrainment, businesses, and the government. IoT is a crucial area that most Research needs to be done on as it gives an idea on the intelligent collaboration of devices can be experienced anywhere and anytime. IoT poses some concerns that make people question its adaptability, and some of the challenges may include data privacy and security. The speed of the growth in devices that need IoT is high, meaning it’s something that has a significant impact on issues on data privacy. The research paper discusses how IoT relates to security and issues in data privacy. It also highlights what the prevalent security threats are in layers of IoT. The Research will be essential to the users in the world and the United States as they can learn how they can make IoT secure and easily adoptable to ensure their devices are protected from malpractices or access to private data from unauthorized people